2022
DOI: 10.1097/phm.0000000000002161
|View full text |Cite
|
Sign up to set email alerts
|

Aging Affects the Efficacy of Platelet-Rich Plasma Treatment for Osteoarthritis

Abstract: Objective: Despite the increased use of platelet-rich plasma in the treatment of osteoarthritis, whether and how age of the platelet-rich plasma donor affects therapeutic efficacy is unclear. Design: In vitro, male osteoarthritic human chondrocytes were treated with platelet-rich plasma from young (18-35 yrs) or old (≥65 yrs) donors, and the chondrogenic profile was evaluated using immunofluorescent staining for two markers of chondrogenicity, type II collagen and SOX-9. In vivo, we used a within-subjects desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The efficacy of PCs is impacted not only by the previously mentioned preparation methods, but also by the age and underlying health conditions of the donors 39 , 40 . Scholars conducted a study using a rat model of myocardial infarction, in which they observed that the application of PRP derived from young donors in combination with BMSCs led to a reduction in the infarct area.…”
Section: Factors Influencing the Efficacy Of The Relevant Treatment A...mentioning
confidence: 99%
“…The efficacy of PCs is impacted not only by the previously mentioned preparation methods, but also by the age and underlying health conditions of the donors 39 , 40 . Scholars conducted a study using a rat model of myocardial infarction, in which they observed that the application of PRP derived from young donors in combination with BMSCs led to a reduction in the infarct area.…”
Section: Factors Influencing the Efficacy Of The Relevant Treatment A...mentioning
confidence: 99%
“…Recognising that older patients may experience a slower healing response underscores the importance of age as a patient-specific factor. This consideration informs clinicians about potential variations in treatment outcomes, allowing for adjustments in treatment plans and setting realistic expectations based on the patient's age-related healing dynamics [ 31 ].…”
Section: Reviewmentioning
confidence: 99%